Enhancing English Speaking Skills of Vocational School Through Project-Based Learning at SMK YPM 5 Sukodono - Handayani, Vinna Putri; Imaniar, Fahmy; Kurniawati, Wiwik (ICONELT, 2024)
Accounting students at SMK YPM 5 Sukodono have a lack of speaking skills in English, this can be seen when students speak in class through presentations. This research focuses on improving accounting students’ speaking skills through in-class presentations as part of PjBL. The aim is to explore how this PjBL method improves students’ English-speaking communication skills. The scope of this research describes the use of PjBL in improving the speaking ability of English language learners in accounting students. This research used the Classroom Action Research (CAR) method in two cycles. The subjects of this study were 35 accounting students including 4 males and 31 females, SMK YPM 5 Sukodono. The study at SMK YPM 5 Sukodono focused on improving English speaking skills among class XI accounting students through mindmap projects and presentations. The results showed a significant improvement in students’ English-speaking skills. The PjBL method has significantly enhanced students’ English-speaking skills through group learning activities. This innovative approach, which encourages students to express their opinions and support each other, has been particularly effective in Cycle I and Cycle II of CAR. The PjBL method promotes fluency, confidence, and enthusiasm in students, thereby boosting their motivation to speak English.